Optimizing Server Monitoring through Graphs Methods using BandwidthD for Two Subnets on a Network - Nasrullah Dahar (University of Sindh Journal of Information and Communication Technology, 2019)
Server monitoring is an essential technique to not only watch overall progress of server machine in terms of efficiency but in other aspects such as the utilization of available resources in an efficient manner. The core of available resources for any network includes Utilization of Server machine speed, RAM, Bandwidth etc. In this research study, bandwidth monitoring of the server machine has been studied in detail from server machine perspective. In the first phase of this research study a proper client server environment has been developed after taking into consideration core aspects of server role in this environment. Thereafter a proper client server environment was created having different subnets to actualize the proper environment for this research study. This research study is based developing graphs for any subnet for any specific network. Graphs of two subnets in specific network shall be developed on the basis of 2-day, 8-day and 40-day period. Results of all protocols in two subnets against bandwidth consumption shall be presented in different color coding of HTTP, TCP/IP, UDP protocols for straightforward server monitoring on windows or Linux platform.